Capacitive deionization with asymmetric electrodes: Electrode capacitance vs electrode surface area. (10th September 2015) - Laxman, Karthik; Gharibi, Laila Al; Dutta, Joydeep
Highlights: Determination of the role of electrode capacitance on the salt adsorption capacity Fabrication of electrodes with distinct surface area and capacitance properties Development of an electrical model to assess salt removal capacity of a CDI cell Optimization of cell and electrode design for maximum salt adsorption capacity ABSTRACT: Asymmetry of electrodes on the equilibrium salt adsorption capacity in a capacitive configuration was studied. Experiments were carried out by using activated carbon cloth (ACC) with a specific surface area and specific capacitance of ∼1000 m 2 /g and 44 F/g as the anode and ACC coated with zinc oxide nanorods (ZnO NR) with a specific surface area and specific capacitance of 637 m 2 /g and 57 F/g as the cathode. The electrodes were characterized electrically and their salt adsorption capacities measured for various anode-cathode configurations to conclude that for multimodal electrodes, specific capacitance and not specific surface area regulates the salt adsorption capacity. The adsorption trends were analyzed and equated to an electrical model to qualitatively predict the equilibrium salt adsorption capacity, where the smaller capacitance was observed to be the limiting factor. The results in this work are especially useful for practical CDI units, where anode-cathode capacitance should be matched to achieve maximum salt removal efficiency.